Pengaruh Pendapatan dan Literasi Keuangan Terhadap Manajemen Keuangan dengan Financial Technology Sebagai Pemediasi - Nurul Fauziyah; Ika Indriasari; Rita Meiriyanti (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to test and analyze the effect of income, financial literacy on financial management with fintech as a mediator. The population in this study were students of the Faculty of Economics and Business. The number of samples in this study was 290 respondents. The sampling technique used simple random sampling technique. The data analysis technique used was PLS-SEM (Partial Least Square- Structural Equation Model) analysis. Research data processing used the Smart-PLS tool. Based on the research results, it was found that income has a positive effect on financial management with a P value of (0.007), income does not have a positive effect on fintech with a P value of (0.114), financial literacy has a positive effect on financial management with a P value of (0.000), financial literacy has a positive effect on fintech with a P value of (0.000), fintech has a positive effect on financial management with a P value of (0.000), financial literacy mediated by fintech has a positive effect on financial management, with a P value of (0.000) and income mediated by fintech does not have a positive effect on financial management, with a P value of (0.118).